The Expected Value of Sampling Information for Linear Decision Problem on Two Actions Under the Ga-E Model for Random Censoring Test - He, Chaobing (International Journal For Research In Mathematics And Statistics, 2020)
Firstly, this paper obtains the likelihood function based on the observed data under the random censoring test, then studies the posterior distribution of parameter of exponential distribution life for the Ga-E model under random censoring test, and focuses on the EVSI calculation formula of linear decision problem on two actions under the GaE model for random censoring test, however, most of the calculations are done using the Monte Carlo method.